Repurchase Intention Konsumen Coffee Shop: Pengujian Peran Moderasi Gaya Hidup pada Packaging dan Cita Rasa - Renita A. Basori; Rizan Machmud; Zulfia K. Abdussamad (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the role of lifestyle as a moderating variable in the relationship between packaging, taste, and consumers' repurchase intention at Fore Coffee in Gorontalo City. The study adopts a quantitative research approach using primary data collected through an online questionnaire distributed to consumers who had previously purchased Fore Coffee products. A purposive sampling technique was employed to select respondents based on predetermined criteria, resulting in a total sample of 97 respondents. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach with SmartPLS version 3.2.9. The findings reveal that packaging has a positive and significant effect on repurchase intention, indicating that attractive, functional, and high-quality packaging encourages consumers to make repeat purchases. Taste also has a positive and significant effect on repurchase intention, suggesting that product quality remains one of the primary determinants of customer loyalty. In addition, lifestyle has a positive and significant effect on repurchase intention, reflecting that consumers whose lifestyles align with the Fore Coffee brand are more likely to repurchase its products. However, the moderation analysis demonstrates that lifestyle does not significantly strengthen or weaken the relationship between packaging and repurchase intention, nor does it moderate the relationship between taste and repurchase intention. These findings imply that while lifestyle directly influences consumers' intention to repurchase, it does not function as a moderating variable in the relationships examined. The study provides practical implications for businesses in the coffee industry, emphasizing the importance of improving packaging quality and maintaining product taste to encourage repeat purchases.